2003
DOI: 10.1111/1469-8986.00078
|View full text |Cite
|
Sign up to set email alerts
|

Effects of positive and negative affect on electromyographic activity over zygomaticus major and corrugator supercilii

Abstract: Pleasant stimuli typically elicit greater electromyographic (EMG) activity over zygomaticus major and less activity over corrugator supercilii than do unpleasant stimuli. To provide a systematic comparison of these 2 measures, the authors examined the relative form and strength of affective influences on activity over zygomaticus major and corrugator supercilii. Self-reported positive and negative affective reactions and facial EMG were collected as women (n = 68) were exposed to series of affective pictures, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

67
632
9
8

Year Published

2005
2005
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 683 publications
(716 citation statements)
references
References 39 publications
67
632
9
8
Order By: Relevance
“…The overall pattern shows that activity in corrugator is potentiated by angry expressions and inhibited by happy expressions. These findings match well with earlier findings (Larsen et al, 2003), demonstrating a linear effect of bipolar emotional valence on corrugator (but not on zygomaticus) EMG activity, with corrugator activity being potentiated by unpleasant pictures and inhibited by pleasant pictures.…”
Section: Facial Emg Responses To Dynamic Emotional Facial Expressionssupporting
confidence: 92%
“…The overall pattern shows that activity in corrugator is potentiated by angry expressions and inhibited by happy expressions. These findings match well with earlier findings (Larsen et al, 2003), demonstrating a linear effect of bipolar emotional valence on corrugator (but not on zygomaticus) EMG activity, with corrugator activity being potentiated by unpleasant pictures and inhibited by pleasant pictures.…”
Section: Facial Emg Responses To Dynamic Emotional Facial Expressionssupporting
confidence: 92%
“…The effect was most pronounced for the corrugator muscle, which showed significantly more activation during the presentation of angry as opposed to happy expressions, while the zygomaticus showed the opposite pattern of activation without individually achieving significance. The weaker effect for the zygomaticus is consistent with studies that found less pronounced differentiations between positive and negative affect for the zygomaticus than the corrugator muscle (Larsen et al, 2003), while other publications report stronger effects for the zygomaticus (Moody & McIntosh, 2011). Since upper and lower face muscles are partly innervated by different brain regions (Adolphs, 2002), it would Unconscious Emotional Facial Activation 15 be worth investigating if these results indicate that reactivity of these muscles are mediated by different processes.…”
Section: Discussionsupporting
confidence: 85%
“…Omnibus tests in the self-report and behavioral domains used univariate repeatedmeasures analyses of variance (ANOVAs) to permit separate examination of indicator variables for happiness and sadness (e.g., zygomatic vs. corrugator EMG; Larsen et al, 2003). Omnibus tests of the physiological domain used multivariate repeated-measures ANOVAs.…”
Section: Hypothesis Testingmentioning
confidence: 99%